When do investors reward acquisitions and divestitures? The contrasting implications of normative and behavioral economic theories. (12th October 2017) - Golder, Peter N.; Markovitch, Dmitri G.; O'Brien, Jonathan P.
Abstract : We evaluate whether a contingency theory that combines a signaling hypothesis with behavioral economic theory can elucidate the discrepancy between positive expected returns to acquisitions and divestitures and the mixed‐to‐negative investor reactions observed in practice. We argue that, because of bounded rationality, uncertainty avoidance, and inertia, major organizational change is generally motivated by the detection of problems in an organization. Accordingly, although investors may view acquisitions and divestitures as positive corrective measures for low performers, such initiatives by high performers often signal problems that were heretofore unknown to the market. We contrast our results with predictions based on normative theories.